A boa fé no regime jurídico de direito administrativo - Nassa, Thulio Caminhoto (2010)
The objective is to prove the good faith before the legal system of administrative law, which infects and that its special design. Justifies the need for its scientific analysis by the fact that, while presenting himself as a fundamental principle of this branch of law, the doctrine does not receive specialized treatment routine. The methodology goes to identify the source of good faith, consider the process of implementing administrative law, its concept and identify differences with other legal institutions so that in the end, it is possible to describe its application in various administrative activities. It is treated in the subjective and objective aspects, and addressed as legal phenomenon of intellectual confidence in the protection of the public interest by the administrator, as the standard of conduct required by law. Developing this thesis, which resulted in good faith is a principle of scientific freedom endowed on administrative law, and deals on virtually all kinds of activity of the state, and receive the case today's big takeover